Association of cancer and Alzheimer's disease risk in a national cohort of veterans. Issue 12 (12th July 2017) - Frain, Laura; Swanson, David; Cho, Kelly; Gagnon, David; Lu, Kun Ping; Betensky, Rebecca A.; Driver, Jane
Abstract: Introduction: To examine the risk of Alzheimer's disease (AD) among cancer survivors in a national database. Methods: Retrospective cohort of 3, 499, 378 mostly male US veterans aged ≥65 years were followed between 1996 and 2011. We used Cox models to estimate risk of AD and alternative outcomes (non‐AD dementia, osteoarthritis, stroke, and macular degeneration) in veterans with and without a history of cancer. Results: Survivors of a wide variety of cancers had modestly lower AD risk, but increased risk of the alternative outcomes. Survivors of screened cancers, including prostate cancer, had a slightly increased AD risk. Cancer treatment was independently associated with decreased AD risk; those who received chemotherapy had a lower risk than those who did not. Discussion: Survivors of some cancers have a lower risk of AD but not other age‐related conditions, arguing that lower AD diagnosis is not simply due to bias. Cancer treatment may be associated with decreased risk of AD. Highlights: Veterans who survived a wide variety of cancers had lower Alzheimer's disease (AD) risk than expected. However, their risk of non‐AD dementia and other diseases was increased. Cancer treatment was independently associated with lower AD risk. Survivors of prostate cancer and melanoma had a slightly increased risk of AD. The lower risk of AD in survivors of some cancers is not due to survival bias.